2003
DOI: 10.1021/la026352w
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Probe Study of Bicelle Structure as a Function of Temperature:  Developing a Practical Bicelle Structure Model

Abstract: Bilayered mixed micelles or bicelles are magnetically anisotropic, self-assembling model membrane structures comprised of long-chain phospholipids and short-chain detergent molecules. In the most widely accepted model of this system, the bicelle is discoid in shape, with the short-chain DHPC molecules aggregating to form rims around long-chain DMPC bilayers. While this model is consistent with most NMR and scattering data (X-ray and neutron), it inadequately describes the liquid-crystalline behavior of bicelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 59 publications
0
56
1
1
Order By: Relevance
“…A disk fusion would be necessary to reach an appropriate size for cooperative alignment (43). Moreover, this model does not reconcile with the increase of viscosity (vide supra) occurring at the temperature at which orientation begins and which suggests the formation of large aggregates (74). According to the results published by several research groups using diverse techniques such as small angle X-ray scattering (SAXS), 31 (77), small-angle neutron scattering (SANS) (56, 78 -80), and fluorescence probe and resonance transfer (FRET) (74), it appears that different oriented and isotropic lipid organizations exist depending on the temperature, lipid concentration, and DMPC/DHPC (q) ratio.…”
Section: Morphologymentioning
confidence: 79%
See 1 more Smart Citation
“…A disk fusion would be necessary to reach an appropriate size for cooperative alignment (43). Moreover, this model does not reconcile with the increase of viscosity (vide supra) occurring at the temperature at which orientation begins and which suggests the formation of large aggregates (74). According to the results published by several research groups using diverse techniques such as small angle X-ray scattering (SAXS), 31 (77), small-angle neutron scattering (SANS) (56, 78 -80), and fluorescence probe and resonance transfer (FRET) (74), it appears that different oriented and isotropic lipid organizations exist depending on the temperature, lipid concentration, and DMPC/DHPC (q) ratio.…”
Section: Morphologymentioning
confidence: 79%
“…According to the results published by several research groups using diverse techniques such as small angle X-ray scattering (SAXS), 31 (77), small-angle neutron scattering (SANS) (56, 78 -80), and fluorescence probe and resonance transfer (FRET) (74), it appears that different oriented and isotropic lipid organizations exist depending on the temperature, lipid concentration, and DMPC/DHPC (q) ratio. In addition, FRET (74) and SANS experiments (56,78), along with tracer diffusion measurements performed by NMR (37), have suggested that oriented bicelles would not adopt a discoidal shape, but undergo edgeto-edge contacts, and this is equivalent to DMPC lamellae perforated by DHPC-stabilized pores (37). This model, also known as the Swiss cheese model (31), is presented in Fig.…”
Section: Morphologymentioning
confidence: 99%
“…in the gel phase, the size of bicelles is small and they are free to perform unrestricted isotropic tumbling [37]. For higher lipids concentration and higher q values the perforated lamellae morphology is also considered [38]. Assuming the bicelle's radius 5.6 nm, determined from our SAXS experiment, the Stokes-Einstein equation yields a ''whole bicelle'' diffusion coefficient of 4.4 10 À11 m 2 /s assuming a water like viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…The high diffusion rate measured for tetramethylsilane (TMS) in oriented bicelles would require extensive transient edge-to-edge contacts in the disk model [156]. Measurements of high viscosity in orientable bicelles [157,158] contradict the theory of individual disks and suggest some entangling. The use of optical microscopy and SANS found yet another bicelle morphology, described as “wormlike micelles” and depicted in Fig.…”
Section: Phase Diagrams and Morphology Of Bicellesmentioning
confidence: 99%